Knowledge Center Initiative for Contributing to Catalyze the Transformation of Engineering Education in India - Jain, Sanjay D.; Nanoti, Vivek M. (Journal of Engineering Education Transformations, 2018)
The processes of imparting and acquiring knowledge, skills and wisdom through educational institutes are key contributors in the cause of national development. However, if we examine the scenario of engineering education in India from this perspective, we find that it has been departing from these primary goals in recent years due to the rigid confinements of marks and degrees. Recently we have taken a knowledge center initiative in our institute that facilitates learning in an open and flexible way using a cafeteria approach that ensures enjoyment, employment, empowerment and enlightenment of learners. In this paper we discuss the impact and growth of this initiative in contributing to transforming education in our institute through development of new and innovative processes of imparting and acquiring knowledge, skills and wisdom that go much beyond the narrow boundaries of marks and degrees. We further discuss how this initiative can also contribute effectively to catalyze the transformation of engineering education in India.